2015
DOI: 10.1007/s11356-015-5405-7
|View full text |Cite
|
Sign up to set email alerts
|

The washout effect during laundry on benzothiazole, benzotriazole, quinoline, and their derivatives in clothing textiles

Abstract: In two previous papers, the authors have shown that benzothiazole, benzotriazole, quinoline, and several of their derivatives are widespread in clothing textile articles. A number of these compounds exhibit allergenic and irritating properties and, due to their octanol-water partition coefficient, are prone to be absorbed by the skin. Moreover, they are slightly soluble in water, which could make washing of clothes a route of emission into the environment. In the present study, the washout effect of benzothiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…The presence of BT in textiles has also been confirmed by other researchers (Liu 2017 ). We have also shown that the concentration of BT decreased in the fabrics when washed, demonstrating a mobility of this chemical from the fabrics (Luongo et al 2016a ). Added together, these results point out a need of appropriate in vitro studies to investigate the release of BT from textile materials and determine if it migrates to, is absorbed by, and/or permeate through the skin.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…The presence of BT in textiles has also been confirmed by other researchers (Liu 2017 ). We have also shown that the concentration of BT decreased in the fabrics when washed, demonstrating a mobility of this chemical from the fabrics (Luongo et al 2016a ). Added together, these results point out a need of appropriate in vitro studies to investigate the release of BT from textile materials and determine if it migrates to, is absorbed by, and/or permeate through the skin.…”
Section: Introductionmentioning
confidence: 60%
“…The LC/MS/MS instrument consisted of an Agilent high-performance liquid chromatography (HPLC) system with a 1260 binary pump, a 1100 degasser, and a 1100 autosampler (Wilmington, DE, USA) coupled to an API QTrap™ triple quadrupole mass spectrometer (PE Sciex, Toronto, ON, Canada) equipped with a TurboIon® electrospray interface operating in positive ion mode. The LC/MS/MS method has been described previously (Luongo et al, 2016a , b ). Briefly, the chromatographic separation was performed using an ACE 3 C8 microbore column (l = 50 mm, i.d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One group of studies reported that TiO 2 and ZnO nanoparticles do not penetrate deeply into the skin. 192 To the contrary, there is evidence of the increase of the 68 Zn isotope in the blood of a healthy adult after exposure to 68 ZnO nanoparticles in a sunscreen formulation. 193 One study reported that healthy skin is a more effective barrier for silver nanoparticles than damaged skin.…”
Section: Pathogenic Microbesmentioning
confidence: 99%
“…121 Such Meinke et al17 extracted fluorescent dyes from a polyester/cotton blend shirt using a sweat simulant and compared the predicted exposure (based on 100% transfer) to that observed in volunteers wearing the shirt during 30 minutes of exercise or for 12 hours of normal activity. In chemical removal during laundering,31,68,92,139 the air-gap between fabric and skin, laundering frequency, and the history of the clothing items prior to wear. A key advantage of dynamic mechanistic models is that they can predict how clothing accumulates chemicals under nonequilibrium conditions.…”
mentioning
confidence: 99%